La recherche sur les systemes agraires ("RSA") au CIPEA - Gryseels, Guido; McIntire, John M.; Anderson, F.M. (1986)
Discusses the historical context of ILCA's research, the principal types of animal production systems and the stages in ILCA's farming systems research. Describes the smallholder farming in the Ethiopian highlands & humid zone, the agropastoralists of the sub-humid zone, systems research in pastoral areas of eastern Africa (Kenya & Ethiopia), characteristics of the arid and semi-arid zones of West Africa and the role of modelling in the system. Ends with a summary of past experience.